2021
DOI: 10.3390/nu13103552
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements for Female Infertility: A Critical Review of Their Composition

Abstract: Infertility is the condition of about 15% of couples that cannot get a conception after one year of unprotected sexual intercourse. In females, the reduced reproductive capacity underlies the most varied causes. Dietary supplements (DS) might be used to improve the pregnancy rate and a wide range of DS are proposed today to support female fertility. Although many authors demonstrated the positive effect of some of these products, the real efficacy of this approach is still debated. In order to evaluate the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…However, most trials used unsatisfactory methodology due to lack of a control group, lack of randomized and placebocontrolled well-designed study, use of many different doses of ingredients, evaluation of different outcomes, small number of included patients, etc. In fact, in the trials concerning male infertility, there is too much focus on the seminological characteristics without taking into consideration the female outcomes and also the pregnancy rate, which should always be our target (69,70). Moreover, many clinical studies were sponsored and analyzed mixtures of many ingredients without evidence of clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, most trials used unsatisfactory methodology due to lack of a control group, lack of randomized and placebocontrolled well-designed study, use of many different doses of ingredients, evaluation of different outcomes, small number of included patients, etc. In fact, in the trials concerning male infertility, there is too much focus on the seminological characteristics without taking into consideration the female outcomes and also the pregnancy rate, which should always be our target (69,70). Moreover, many clinical studies were sponsored and analyzed mixtures of many ingredients without evidence of clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many clinical studies were sponsored and analyzed mixtures of many ingredients without evidence of clinical efficacy. However, these supplements are frequently prescribed in clinical practice to infertile patients, and sometimes, subjects seeking fertility spontaneously purchase these products since medical prescription is unnecessary (70). In 2019, the Italian market of supplements generated 3.7 billion euros, with an increase of +4.3% compared to 2018 (71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence of a relationship between diet and female fertility and of a lower fruit intake with infertility has increasingly accummulated (Skoracka et al 2021 ). To improve their chances of conception, many women request treatment with dietary supplements with variable ingredients (Vitagliano et al 2021 ). A systematic review by Salas-Huetos et al indicated that daily diets rich in some antioxidant nutrients, such as vitamin C, vitamin E, selenium, and zinc, were inversely associated with low semen quality parameters (Salas-Huetos et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%